Economic evaluation of carbetocin as prophylaxis for postpartum hemorrhage in the Philippines - Jamaica Roanne Briones; Pattarawalai Talungchit; Montarat Thavorncharoensap; Usa Chaikledkaew (BMC, 2020)
Abstract Background The World Health Organization (WHO) recommends oxytocin as the drug of choice for postpartum hemorrhage (PPH) prevention. However, the WHO has also recently considered carbetocin for PPH prevention, but only if carbetocin were a cost-effective choice in the country. Consequently, we determined the cost-effectiveness and budgetary impact of carbetocin against oxytocin in the Philippines. Methods A cost-utility analysis using a decision tree was done to compare the costs and outcomes of carbetocin with oxytocin for PPH prophylaxis among women undergoing either vaginal delivery (VD) or cesarean section (CS) in a six-week time horizon using a societal perspective. One-way and probabilistic sensitivity analyses were applied to investigate parameter uncertainties. Additionally, budget impact analysis was conducted using a governmental perspective. Results were presented as incremental cost-effectiveness ratio (ICER) using a 2895 United States dollar (USD) per quality adjusted life year (QALY) gained as the ceiling threshold in the Philippines. Results Carbetocin was not cost-effective given the listed price of carbetocin at 18 USD. Given a societal perspective, the ICER values of 13,187 USD and over 40,000 USD per QALY gained were derived for CS and VD, respectively. Moreover, the ICER values were sensitive to the risk ratio of carbetocin versus oxytocin and carbetocin price. On budget impact, the five-year total budget impact of a drug mix of carbetocin and oxytocin was 25.54 million USD (4.23 million USD for CS and 21.31 million USD for VD) compared with 'only oxytocin' scenario. Conclusion Carbetocin is not a cost-effective choice in PPH prevention for both modes of delivery in the Philippines, unless price reduction is made. Our findings can be used for evidence-informed policies to guide coverage decisions on carbetocin not only in the Philippines but also in other low and middle-income countries.